2020
DOI: 10.3390/cancers12020518
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Normalization Approaches to Automatically Detect Radiogenomic Phenotypes Characterizing Breast Cancer Receptors Status

Abstract: In breast cancer studies, combining quantitative radiomic with genomic signatures can help identifying and characterizing radiogenomic phenotypes, in function of molecular receptor status. Biomedical imaging processing lacks standards in radiomic feature normalization methods and neglecting feature normalization can highly bias the overall analysis. This study evaluates the effect of several normalization techniques to predict four clinical phenotypes such as estrogen receptor (ER), progesterone receptor (PR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 73 publications
1
46
0
Order By: Relevance
“…Data normalization methods are important in both radiomic and genomic field, due to their inner differences in range, scale and statistical distributions. Non-normalized features might present high levels of skewness, resulting in misleading low p values in statistical investigation 33 , 34 . Lately, normalization techniques are of great interest in data preprocessing especially for machine learning algorithms 35 .…”
Section: Methodsmentioning
confidence: 99%
“…Data normalization methods are important in both radiomic and genomic field, due to their inner differences in range, scale and statistical distributions. Non-normalized features might present high levels of skewness, resulting in misleading low p values in statistical investigation 33 , 34 . Lately, normalization techniques are of great interest in data preprocessing especially for machine learning algorithms 35 .…”
Section: Methodsmentioning
confidence: 99%
“…In the last decades, the increasing number of biobanks infrastructures (Coppola et al, 2019 ) has allowed the prompt availability of quality-controlled biological samples to be processed using next-generation sequencing (NGS) technologies (Chakraborty et al, 2018 ). The advent of NGS technologies and radiomics has revolutionized the approach to study disease biology, augmenting precision oncology (Incoronato et al, 2017 ; Zanfardino et al, 2019a , b ; Castaldo et al, 2020 ). In BC research, the integration of NGS technologies with cutting-edge approaches might help to decipher also other tumor-relevant aspects such as immune and stromal component, microbiome, and urobiome modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows a summary of the topics and the papers included for each topic [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. The majority of papers are focused on prostate cancer (PCa) and radiomics.…”
mentioning
confidence: 99%
“…In the last years, a large amount of data has been published, such as in the current issue of Cancers , in order to apply this in diverse settings of disease. Castaldo et al [ 30 ] and Schiano et al [ 32 ] evaluated the role of radiomics in breast cancer. The first group of authors concluded the ability of radiomic features by MRI to discriminate major breast cancer molecular subtypes, thus potentially guiding a personalized treatment [ 30 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation